Infertility-related stress and sexual satisfaction: a dyadic approach. (2nd January 2022) - Nakić Radoš, Sandra; Soljačić Vraneš, Hrvojka; Tomić, Jozo; Kuna, Krunoslav
Abstract: Purpose of the study: to examine whether women's and men's infertility-related stress, and specifically its sexual concerns aspect, is related to their and their partner's sexual satisfaction. Materials and methods: In a cross-sectional study, 94 couples experiencing infertility filled out the New Sexual Satisfaction Scale and Fertility Problem Inventory, which measures infertility-related stress with dimensions of social, sexual and relationship concerns, rejection of childfree lifestyle, and need for parenthood. Dyadic analyses were performed following the Actor-Partner Interdependence Model (APIM). Results: The dyadic analysis revealed that women's and men's greater infertility-related stress contributed to their lower levels of sexual satisfaction (actor effect). Moreover, women's and men's greater sexual concerns (as the aspect of infertility-related stress) contributed to their own and their partner's lower levels of sexual satisfaction (actor and partner effect). Conclusions: The findings suggest that both individual and relational processes are important in the association between the specific dimension of infertility-related stress and sexual satisfaction. These findings could guide the psychosocial support for couples experiencing infertility.